Diagnostic Assessment Instrument for Arabic Vocabulary Comprehension Using Crossword Puzzle - Rahmawati, Rahmawati; Hasibuan, Renni; Jundi, Muhammad; Sari, Ranita (Universitas Negeri Padang, 2024)
Diagnostic assessment is a crucial element in the implementation of the Merdeka Curriculum. This study aims to design a diagnostic instrument for Arabic language students in grade 7 at MTs. N Batu using Arabic vocabulary crossword puzzles and analyzing the assessment results for follow-up planning. The approach employed is a combination of quantitative and qualitative methods. Data were obtained through observation, interviews, and tests. The findings indicate that designed diagnostic assessment instrument has good content validity and is relevant to the curriculum. The use of instrument in teaching is considered efficient and effective. However, the analysis results show that most students still have low vocabulary proficiency. Several errors and weaknesses in vocabulary usage were also identified, such as incorrect use of writing vocabularies letters. It is hoped the findings of this diagnostic assessment analysis can serve as a basis for improving the quality of Arabic language learning in the future, particularly in terms of vocabulary mastery.